CHINA AND THE SECURITY OF SOUTHEAST ASIA - Swanstrom, Niklas (Penerbit USM, 2000)
This paper deals with foreign policy of China towards Southeast Asia and the implications it has on the security of Southeast Asia after the Asian financial crisis.